Properties Of Esterified Κ-Carrageenan And Esterified Κ-Carrageenan-Zirconia Composite Material - Teow, Cheng Yee (2012)
A new method which does not involve the use of water as solvent for esterification of carrageenan, was developed to synthesize κ-carrageenan esters. Pyridine was used as solvent and catalyst in this synthesis. The effect of temperature and amount of decanoyl chloride to the esterification process was studied systematically in this work. Characterisation by Fourier Transforms Infra-Red Spectrometer (FTIR) and Nuclear Magnetic Resonances Spectrometer (NMR) techniques revealed the formation of ester bond in all samples. The glass transition temperatures, Tg of κ-carrageenan esters which were studied using Differential Scanning Calorimetry (DSC) and the result revealed that all the κ-carrageenan esters synthesized have lower glass transition temperature than the κ-carrageenan. By using 1H-NMR spectra, the degree of substitution of acyl group was determined to be highest at 90 oC reaction temperature. The optimum amount of acyl chloride used to prepared κ-carrageenan ester with the highest degree of substitution was determined to be 0.175 mol. All κ-carrageenan esters show good solubility in toluene but not in water. Further purification of the esters using sodium bicarbonate and toluene yield a purer κ-carrageenan ester. κ-carrageenan ester synthesized without further purification was used in the preparation of κ-carrageenan ester and zirconia composite using the sonication technique. The composite which is insoluble in water and toluene, showed better thermal properties as compared to κ-carrageenan esters.